Equine chorionic gonadotrophin influences on follicular development, ovulation rate and gestational development in cross-bred goats - Mohamad Mohtar, Mohamad Shuib (2012)
Superovulation techniques are usually conducted to enhance ovarian follicular activity and subsequently increase reproductive efficiency in goat breeding. This study was carried out to depict the effects of a superovulation technique using equine chorionic gonadothrophin (eCG) treatment on increasing follicular growth, ovulation rate and numbers of kid born. In this study, 29 non-pregnant pluriparous Boer does weighing between 45 and 65 kg, with good body condition were randomly selected and allocated into 3 groups, namely Group 1 (G1, n=11), Group 2 (G2, n=8) and Group 3 (G3, n=10). All does were synchronized using CIDR containing 0.3 g progesterone intravaginally for 18 days. Blood samples from every doe were collected from the jugular vein using test tubes containing heparin during CIDR treatment (Day 0, 6, 13, 18) and post CIDR treatment (Day 19, 20, 27, 34, 41 and 48). On Day 17 of the CIDR treatment, superovulation treatment using eCG was given intramuscularly using three different treatment dosages. Does in G1, G2 and G3 received 600 IU, 800 IU and 1000 IU eCG, respectively on the same days. Follicular identification on the left and right ovary was conducted using transrectal ultrasonography technique for 4 consecutive days starting on Day 17 of the CIDR treatment. After CIDR removal, oestrus responses in all does were recorded and natural mating was conducted. After 7 days post-mating, the transrectal ultrasonography technique was applied to identify the numbers of corpora lutea present in each side of the ovary. Subsequently, pregnancy diagnosis was carried out using transrectal ultrasonography technique at 30 days post-mating. Measurements of sizes of placentomes were carried out using transrectal ultrasonography on Day 42, 49, 56 and 63 of pregnancy. Data of does kidded were collected after the pregnancy period. Result of the study showed that the range of percentage of does showing oestrus within 48 h after CIDR removal in the three groups was 62.5% to 81.8%. The G1 does (54.5%) had a significantly higher (P< 0.05) compared to G2 (25%) and G3 (20%) oestrus response within 24 h after CIDR removal. No significant differences among treatments were observed in terms of the number of follicles developed except for small sized follicles on Day 19 and 20. Meanwhile, the G2 does had the highest ovulation rate (P< 0.05) of 2.38 ± 0.32 CL compared to G3 (1.6 ± 0.22 CL) and G1 (1.45 ± 0.15 CL). The average pregnancy rate showed 11 out of 21 oestrus does were pregnant (52.4%) with G3 does (71.4%) having the highest pregnancy rate compared to the other groups at 55.5% (G1) and 20% (G2). Based on progesterone concentration analysis, all treatments does except unsuccessful mated does in G3 showed increasing level of progesterone starting on Day 0 (CIDR inserted) until next 6 days. After Day 6, the progesterone level for all treatments does have continuously decline until Day 18 (CIDR removal), 19 and lastly Day 20. Only after Day 20, the progesterone level was tremendously increased and maintains above 20 ng/ml until 30 days pregnancy in successful mated does. Whereas, for unsuccessful mated does their progesterone level was peak on Day 34 before decline lower than 5 ng/ml until Day 48. Significant differences in the progesterone level were observed between pregnant and non-pregnant does at Day 41 pregnancies for G1 and at Day 48 for G2 and G3 does post-CIDR insertion. No significant differences were observed among treatments in terms of the size of placentomes (in early stage of pregnancy), kidding rate and gestation length. In conclusion, superovulation by eCG with a long term progesterone treatment in goats has increased the ovulatory activity to produce more matured follicles, high oestrous response and twinning rate. However, this thesis also revealed that the growth of placentome and gestation length were not affected by the different dosages of eCG.